Analisis Pengaruh CAR, LDR, BOPO, NPL Terhadap Pertumbuhan Laba Pada Sektor Perbankan - Annisya, Dhea; Munandar, Aris; Ratu, Mutiara Kemala (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to analyze the influence of CAR, LDR, BOPO, NPL on profit growth in the banking sector. This research aims to evaluate how much each variable influences profit performance, as well as understanding the interactions between these variables. In addition, it is hoped that this research can provide practical recommendations for bank managers in improving efficiency and risk management to achieve better profit growth. This research uses quantitative analysis. The sample used was 43 companies. The data obtained in this research was from banking sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. The data analysis technique uses descriptive statistical analysis, with t test and hypothesis testing using e-views. The research results show that the CAR variable partially has a positive and significant effect on Profit Growth, the LDR and BOPO variables partially have a negative and significant effect on Profit Growth, the NPL variable partially has a positive and insignificant effect on Profit Growth.This research aims to analyze the influence of CAR, LDR, BOPO, NPL on profit growth in the banking sector. This research aims to evaluate how much each variable influences profit performance, as well as understanding the interactions between these variables. In addition, it is hoped that this research can provide practical recommendations for bank managers in improving efficiency and risk management to achieve better profit growth. This research uses quantitative analysis. The sample used was 43 companies. The data obtained in this research was from banking sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. The data analysis technique uses descriptive statistical analysis, with t test and hypothesis testing using e-views. The research results show that the CAR variable partially has a positive and significant effect on Profit Growth, the LDR and BOPO variables partially have a negative and significant effect on Profit Growth, the NPL variable partially has a positive and insignificant effect on Profit Growth.